2012
DOI: 10.4103/1477-3163.100866
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycogen synthase kinase 3β in the development of pancreatic cancer

Abstract: Development and progression of pancreatic cancer involves general metabolic disorder, local chronic inflammation, and multistep activation of distinct oncogenic molecular pathways. These pathologic processes result in a highly invasive and metastatic tumor phenotype that is a major obstacle to curative surgical intervention, infusional gemcitabine-based chemotherapy, and radiation therapy. Many clinical trials with chemical compounds and therapeutic antibodies targeting growth factors, angiogenic factors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…We and others have shown that GSK-3 β is progressively overexpressed during progression from pancreatic intraepithelial neoplasia to advanced PDA and is localized to the nucleus in most moderately and poorly differentiated tumors. 23 , 24 , 25 , 26 Additionally, it has been observed that GSK-3 β overexpression contributes to PDA cell proliferation and survival, whereas GSK-3 inhibition reduces pancreatic cancer cell viability in vitro and suppresses tumor xenograft growth in vivo , at least partly, via downregulation of NF- κ B activity. 23 , 24 , 25 , 26 , 27 , 28 In view of the impact of NF- κ B target genes on TRAIL-induced apoptosis, we have assessed the impact of GSK-3 inhibition or downregulation on TRAIL-induced killing and have examined the mechanism of GSK-3 inhibitor (GSK-3i)-mediated TRAIL sensitization in PDA cells.…”
mentioning
confidence: 99%
“…We and others have shown that GSK-3 β is progressively overexpressed during progression from pancreatic intraepithelial neoplasia to advanced PDA and is localized to the nucleus in most moderately and poorly differentiated tumors. 23 , 24 , 25 , 26 Additionally, it has been observed that GSK-3 β overexpression contributes to PDA cell proliferation and survival, whereas GSK-3 inhibition reduces pancreatic cancer cell viability in vitro and suppresses tumor xenograft growth in vivo , at least partly, via downregulation of NF- κ B activity. 23 , 24 , 25 , 26 , 27 , 28 In view of the impact of NF- κ B target genes on TRAIL-induced apoptosis, we have assessed the impact of GSK-3 inhibition or downregulation on TRAIL-induced killing and have examined the mechanism of GSK-3 inhibitor (GSK-3i)-mediated TRAIL sensitization in PDA cells.…”
mentioning
confidence: 99%
“…However, GSK-3β itself plays different roles in different cases. Previous studies have shown that GSK-3β overexpression plays key roles in multiple types of cancer, including ovarian cancer [ 22 ], breast cancer [ 23 ], pancreatic cancer [ 24 26 ], colon cancer [ 27 ], bladder cancer [ 28 ], myeloma [ 29 ] and leukaemia [ 30 ]. Sun et al reported that GSK-3β controls PCa cell autophagy and that GSK-3β inhibition triggers autophagy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have also demonstrated therapeutic effects against the respective cancer types using various pharmacological GSK3β inhibitors including lithium, natural products and medicines with GSK3β-inhibiting activity, and GSK3β-specific short interfering (si) or short hairpin (sh)RNA that are highly selective for GSK3β inhibition. The most extensively investigated cancer types to date are colon and rectum [ 161 ], pancreas [ 162 , 163 , 164 , 165 ] and prostate [ 166 ], as well as glioblastoma [ 167 , 168 , 169 ] and leukemia [ 170 , 171 , 172 ]. Compared to GSK3β, only a few studies have investigated the tumor-promoting role of GSK3α, another isoform of the GSK3 family, in pancreatic cancer and acute myeloid leukemia [ 173 , 174 , 175 ].…”
Section: Tumor-promoting Roles Of Gsk3β In Various Cancer Typesmentioning
confidence: 99%